Establishing conservation units to promote recovery of two threatened freshwater mussel species (Bivalvia: Unionida: Potamilus). Issue 16 (31st July 2021) - Smith, Chase H.; Johnson, Nathan A.; Robertson, Clinton R.; Doyle, Robert D.; Randklev, Charles R.
Abstract: Population genomics has significantly increased our ability to make inferences about microevolutionary processes and demographic histories, which have the potential to improve protection and recovery of imperiled species. Freshwater mussels (Bivalvia: Unionida) represent one of the most imperiled groups of organisms globally. Despite systemic decline of mussel abundance and diversity, studies evaluating spatiotemporal changes in distribution, demographic histories, and ecological factors that threaten long‐term persistence of imperiled species remain lacking. In this study, we use genotype‐by‐sequencing (GBS) and mitochondrial sequence data (mtDNA) to define conservation units (CUs) for two highly imperiled freshwater mussel species, Potamilus amphichaenus and Potamilus streckersoni . We then synthesize our molecular findings with details from field collections spanning from 1901 to 2019 to further elucidate distributional trends, contemporary status, and other factors that may be contributing to population declines for our focal species. We collected GBS and mtDNA data for individuals of P. amphichaenus and P. streckersoni from freshwater mussel collections in the Brazos, Neches, Sabine, and Trinity drainages ranging from 2012 to 2019. Molecular analyses resolved disputing number of genetic clusters within P. amphichaenus and P. streckersoni ; however, we find defensible support for four CUs, each corresponding to an independent river basin. Evaluations of historical and recent occurrence data illuminated a generally increasing trend of occurrence in each of the four CUs, which were correlated with recent increases in sampling effort. Taken together, these findings suggest that P. amphichaenus and P. streckersoni are likely rare throughout their respective ranges. Because of this, the establishment of CUs will facilitate evidence‐based recovery planning and ensure potential captive propagation and translocation efforts are beneficial. Our synthesis represents a case study for conservation genomic assessments in freshwater mussels and provides a model for future studies aimed at recovery planning for these highly imperiled organisms. Abstract : Freshwater mussels (Bivalvia: Unionida) represent one of the most imperiled groups of organisms globally. In this study, we couple multiple molecular datasets with survey data to facilitate recovery efforts for two threatened species of freshwater mussels. Our synthesis represents a case study for conservation genomic assessments in freshwater mussels and provides a model for future studies aimed at recovery planning for these highly imperiled organisms.